Treatment of rubberwood (Hevea brasiliensis) (Willd. ex A. Juss.) Müll. Arg. with maleic anhydride to prevent moulds - K. Oldertrøen; A. H-Kittikun; S. Phongpaichit; S. Riyajan; R. Teanpaisal (Journal of Forest Science, 2016)
The rubberwood samples were treated with 0.5-10% maleic anhydride (MA) solutions. The treatment of wood with 2.5% MA was adequate to prevent the growth of moulds on wood for 1 year at least. The viable count of Aspergillus niger van Tieghem PSU1 on MA treated wood indicated that fungal spores were not killed. The maleic anhydride treated wood slices had no antifungal activity. The concentration of MA released from treated wood in the leachate was 0.02 mg.m-3. Agar well diffusion showed that the leachate from MA treated wood had no antifungal activity. However, after leaching MA treated wood still had a high resistance to mould growth. The moisture contents of MA treated and untreated wood samples were not significantly different. The MA treated wood showed almost a smooth surface while the untreated wood showed a rough surface. The cytotoxicity test showed that the leachates of both MA treated and untreated wood samples had a similar effect. So the treatment of rubberwood with MA is a safe method to prevent mould growth.